2020
DOI: 10.1097/mcg.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communication in Outpatient Consultations in People With Cirrhosis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Verbal endorsement of question‐asking alone may not increase question asking by the patient, 24–27 so other methods such as the introduction of Question Prompt Lists (QPLs) should be considered. QPLs are a list of prompting questions that may be relevant to the patient during their consultation, 28 and they are a favourable communication tool by both patients and doctors 28–30 . QPLs increase the number of questions asked by the patient and have minimal impact on consultation time 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal endorsement of question‐asking alone may not increase question asking by the patient, 24–27 so other methods such as the introduction of Question Prompt Lists (QPLs) should be considered. QPLs are a list of prompting questions that may be relevant to the patient during their consultation, 28 and they are a favourable communication tool by both patients and doctors 28–30 . QPLs increase the number of questions asked by the patient and have minimal impact on consultation time 31 …”
Section: Discussionmentioning
confidence: 99%
“…QPLs are a list of prompting questions that may be relevant to the patient during their consultation, 28 and they are a favourable communication tool by both patients and doctors. [28][29][30] QPLs increase the number of questions asked by the patient and have minimal impact on consultation time. 31 Time-pressures perceived by patients through the surgeons' conduct could prevent patients asking questions.…”
Section: Surgeon/consultation Factorsmentioning
confidence: 99%
“…However, decisions regarding life-prolonging treatments are also relevant for patients with other advanced diseases, such as advanced stages of chronic obstructive pulmonary disease, chronic heart failure, 45 chronic kidney disease 46 or liver disease. 47 It is known that in adults with advanced diseases, options for starting, stopping or forgoing life-prolonging treatments are often discussed only at a late stage due to discomfort about addressing end-of-life issues and uncertainty about the timing of such discussions. 16 45 48 Besides, healthcare professionals are often uncertain about how to address a poor prognosis or a short life expectancy, which might result in them avoiding these topics, even though those conversations may have consequences for treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a question prompt list, a recommended set of questions that patients and their family can review prior to an outpatient visit regarding their medical care, has been shown to improve communication among providers, patients, and families [47]. A question prompt list has recently been developed for patients with advanced liver disease and could provided to patients in the outpatient setting prior to a clinic appoint to empower them to express their unmet informational needs [48]. Use of visual aids such as the "Best case/Worst case" communication tool to provide anticipatory guidance for patients with advanced liver disease should be considered and has been shown to be effective in shared decision-making and ACP in patients with serious illnesses [41 Collaborating with specialty palliative care services in the outpatient setting may be helpful to clarify patients' goals and values early in their disease course.…”
Section: How To Integrate Early Acp Into Outpatient Hepatology Clinical Practicementioning
confidence: 99%